2019
DOI: 10.1097/cin.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cost of Virtual Reality Training and Live Exercises for Training Hospital Workers for Evacuation

Abstract: Adoption of virtual reality technology may be delayed due to high up-front costs with unknown returns on that investment. In this article, we present a cost analysis of using virtual reality as a training tool. Virtual reality was used to train neonatal intensive care workers in hospital evacuation. A live disaster exercise with mannequins was also conducted that approximated the virtual experience. Comparative costs are presented for the planning, development, and implementation of both interventions. Initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 13 publications
1
97
0
4
Order By: Relevance
“…The non-immersive equipment and semi-immersive equipment are easier to apply as a means of therapy and can be used as home care intervention ( 61 , 63 ). Even though this variable was not evaluated in this review, currently, the ER intervention especially with VR equipment is more expensive than CPT, but in the future, financial affordability is expected, which will enable easier access for the population overall and will facilitate its usage as a rehabilitation method ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…The non-immersive equipment and semi-immersive equipment are easier to apply as a means of therapy and can be used as home care intervention ( 61 , 63 ). Even though this variable was not evaluated in this review, currently, the ER intervention especially with VR equipment is more expensive than CPT, but in the future, financial affordability is expected, which will enable easier access for the population overall and will facilitate its usage as a rehabilitation method ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lechermeier and Fassnacht [ 34 ] found that feedback from professionals of higher status and expertise was still the most effective in training. However, the cost of virtual simulation systems is lower when used for a long time [ 35 ]. Third, the result obtained in this survey show students reported greater levels of satisfaction for the combination teaching methods than the students assigned to the traditional teaching method condition.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lechermeier and Fassnacht [34] found that feedback from professionals of higher status and expertise was still the most effective in training. However, the cost of virtual simulation systems is lower when used for a long time [35].…”
Section: Discussionmentioning
confidence: 99%